Immobilization of Fibronectin-Loaded Polyelectrolyte Nanoparticles on Cardiovascular Material Surface to Improve the Biocompatibility - Liu, Shihui (Biomed Res Int, 2019)
Vascular stent interventional therapy is the main method for clinical treatment of coronary artery diseases. However, due to the insufficient biocompatibility of cardiovascular materials, the implantation of stents often leads to serious adverse cardiac events. Surface biofunctional modification to improve the biocompatibility of vascular stents has been the focus of current research. In this study, based on the structure and function of extracellular matrix on vascular injury healing, a novel fibronectin-loaded poly-l-lysine/heparin nanoparticles was constructed for stent surface modification. In vitro blood compatibility evaluation results showed that the nanoparticles-modified surface could effectively reduce platelet adhesion and activation. In vitro cellular compatibility evaluation results indicated that the nanocoating may provide adequate efficacy in promoting the adhesion and proliferation of endothelial cells and thereby accelerate endothelialization. This study provides a new approach for the surface biological function modification of vascular stents.